81.4k views
3 votes
7x+8y=10 5x+y=−7 solve by elimination

User Atypical
by
5.7k points

2 Answers

2 votes

Answer:

The solution is x = -2, y = 3. As an ordered pair it is (-2, 3).

Explanation:

7x + 8y = 10

5x + y = −7

Multiply the second equation by -8:

-40x - 8y = 56

Add this to the first equation, we get:

-33x = 66

x = -2

Now substitute for x in the second equation:

5(-2) + y = -7

y = -7 + 10

y = 3.

Check these results in the first equation:

7(-2) + 8(3) = -14 + 24 = 10 - so correct.

User Artur Pyszczuk
by
5.1k points
3 votes

Answer:

(-2,3)

Explanation:

7x+8y=10

5x+y=-7

To solve this by elimination, we need both equations in the same form. There are. They are both in form ax+by=c.

Now we also need for one of the columns with the variables to be opposite or same terms.

I like the way the column with the y's are looking because if I multiply that second y by 8 or -8 I will have sames or opposites.

I'm going to multiply the second equation by -8.

This will give me:

7x+8y=10

-40x-8y=56

--------------------Add the equations!

-33x+0=66

-33x =66

x =66/-33

x =-2

Now we need to find the other variable. It doesn't matter which equation you use.

I'm going to use 5x+y=-7 where x=-2 to find y.

5(-2)+y=-7

-10+y=-7

Add 10 on both sides

y=3

The solution is (-2,3)

User Nazeem
by
5.5k points